Cumulative 5-year Results of a Randomized Controlled Trial Comparing Biological Mesh With Primary Perineal Wound Closure After Extralevator Abdominoperineal Resection (BIOPEX-study). Issue 1 (January 2022) - Blok, Robin D.; Sharabiany, Sarah; Stoker, Jaap; Laan, Ellen T. M.; Bosker, Robbert J. I.; Burger, Jacobus W. A.; Chaudhri, Sanjay; van Duijvendijk, Peter; van Etten, Boudewijn; van Geloven, Anna A. W.; de Graaf, Eelco J. R.; Hoff, Christiaan; et al.
Abstract : Objective: To determine long-term outcomes of a randomized trial (BIOPEX) comparing biological mesh and primary perineal closure in rectal cancer patients after extralevator abdominoperineal resection and preoperative radiotherapy, with a primary focus on symptomatic perineal hernia. Summary Background Data: BIOPEX is the only randomized trial in this field, which was negative on its primary endpoint (30-day wound healing). Methods: This was a posthoc secondary analysis of patients randomized in the BIOPEX trial to either biological mesh closure (n = 50; 2 dropouts) or primary perineal closure (n = 54; 1 dropout). Patients were followed for 5 years. Actuarial 5-year probabilities were determined by the Kaplan-Meier statistic. Results: Actuarial 5-year symptomatic perineal hernia rates were 7% (95% CI, 0–30) after biological mesh closure versus 30% (95% CI, 10–49) after primary closure ( P = 0.006). One patient (2%) in the biomesh group underwent elective perineal hernia repair, compared to 7 patients (13%) in the primary closure group ( P = 0.062). Reoperations for small bowel obstruction were necessary in 1/48 patients (2%) and 5/53 patients (9%), respectively ( P = 0.208). No significant differences were found for chronic perineal wound problems, locoregional recurrence, overall survival, and main domains of quality of life and functional outcome. Conclusions: Symptomatic perineal hernia rate at 5-year follow-up after abdominoperineal resection for rectal cancer was significantly lower after biological mesh closure. Biological mesh closure did not improve quality of life or functional outcomes. Abstract : Supplemental Digital Content is available in the text